Efficiency of bronopol and kathon in preservation of milk and milk products samples stored for analytical purpose - Mitul, Bumbadiya; Amit, Chilbule; Singh, Richa; Arora, Sumit; Mann, Bimlesh; Rao, Priyanka Singh (Indian Journal of Dairy Science, 2020)
Formalin (0.4%) is the only legally permitted preservative by FSSAI for preservation of milk and milk product samples which are kept for analytical analysis. However, formalin is reported to interfere with the estimation of milk fat which results in lower fat values than original. In the present investigation, the efficiency of bronopol and kathon was evaluated in preservation of milk and milk products. Bronopol and kathon both are broad spectrum antimicrobial compounds. Kathon (0.40%) and bronopol (0.40%) did not have significant effect on fat, SNF and protein content. However, lactose content increased significantly in milk samples added with kathon. A preservative formulation (combination of kathon and bronopol) was standardized and addition of 0.6% it, all microbiological counts were nil in first dilution as well as there was no significant effect on fat, SNF, lactose and protein content of milk. Moreover, on addition of this preservative formulation 1.0 1.2 and 1.2 % in khoya, paneer and dahi samples respectively, there was a significant reduction of microbiological counts of khoya, paneer and dahi. The optimized formulation (combination of bronopol and kathon) was found to be stable at 37 Â°C as well as refrigeration temperature for 120 days in amber colour bottle based on microbiological study.